HPTLC Fingerprinting: A Tool for Simplified Analysis of Phenolics in Medicinal Plants - Saraf, Amit Yadaorao; Saraf, Aparna Amit (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Phenolic compounds especially the flavonoids and tannins comprise one of the most significant classes of plant secondary metabolites. Aim: HPTLC is widely accepted by WHO and pharmacopoeia across the globe as an effective analytical method for the investigation of phenolics in herbal analyses. Materials and Methods: The methanolic extracts of Abrus precatorius L., Sapindus trifoliatus L. and Embelia ribes Burm. F. were developed on the HPTLC system to study the diversity of phenolic compounds like flavonoids and tannins under different development conditions. Flavanoids were separated using the combination of solvent system comprising of mid-polar to polar solvents, hence Ethyl acetate: formic acid: glacial acetic acid: water (10:0.5:0.5:1 v/v/v/v) solvent mixture and 10% methanolic Sulphuric Acid Reagent was used as spray reagent for separation of flavanoids. Tannins were separated on chromatogram by using the solvent system comprising of mid-polar to non-polar solvents, hence Toluene: Ethyl Acetate: Formic Acid (6:4:0.3 v/v/v) as solvent system and alcoholic FeCl3 was used for derivatization. Results: Distinct fingerprint of flavanoids and tannins was obtained. A profile of 11 to 12 polyvalent phytoconstituents were separated during the HPTLC analysis of flavonoids and tannins respectively. Conclusion: The HPTLC analysis successfully demonstrated that phenolic secondary metabolites can be effectively separated using the same extract under different development conditions. The detection and profiling of such metabolites provides the justification for therapeutic activities in medicinal plants.
Keywords: HPTLC; Flavonoids; Tannins; Abrus precatorius L; Sapindus trifoliatus L; Embelia ribes Burm. F